Adverse effects of exposure to ambient air pollution on coronary calcification. (25th November 2020) - Huynh, Q; Venkataraman, P; Marwick, T.H; Negishi, K
Abstract: Background: The association of air pollution with cardiovascular morbidity and mortality has been attributed to acute events (atherothrombosis). It is unclear whether air pollution may influence the subclinical stage of coronary artery disease (CAD). This study investigated the relationship between particulate matter <2.5μm (PM2.5) and nitrogen dioxide (NO2) with coronary calcium score (CCS). Methods: This study included 606 asymptomatic adults (49% men, aged 56±7 years) recruited from the community in two States of Australia (Victoria and Tasmania). Annual PM2.5 and NO2 concentrations were matched with residential address. CCS was measured using coronary CT scan. Medical history, physical measurements, biochemistry, and socioeconomic status were recorded for assessment of confounders. Results: Average exposure to PM2.5 and NO2 were 6.7±1.5 (ppm) and 3.6±2.1 (μg/m 3 ), respectively. Of the 606 participants, 17% had high CCS (≥100) and 4% had very high CCS (≥400). Exposure to higher annual PM2.5 was associated with greater odds of high CCS (OR=1.20 [95% CI: 1.02, 1.42]) and very high CCS (OR=1.47 [95% CI: 1.03, 2.11]). Similar adverse associations were also present for NO2 and high CCS (OR=1.13 [95% CI: 1.02, 1.25]) and very high CCS (OR=1.25 [95% CI: 1.06, 1.47]). These findings were independent of age, sex, body size, smoking, comorbidities and socio-economic status. Conclusions: Ambient air pollution was associated with degree of coronary calcification, independent of standard risk factors. The link between air pollution and CAD is not limited to acute events but appears to include atherogenesis. Funding Acknowledgement: Type of funding source: None